A thioredoxin NbTRXh2 from Nicotiana benthamiana negatively regulates the movement of Bamboo mosaic virus - Chen, I‐Hsuan; Chen, Hui‐Ting; Huang, Ying‐Ping; Huang, Hui‐Chen; Shenkwen, Lin‐Ling; Hsu, Yau‐Heiu; Tsai, Ching‐Hsiu (Molecular plant pathology, 2018)
Summary An up‐regulated gene derived from Bamboo mosaic virus (BaMV)‐infected Nicotiana benthamiana plants was cloned and characterized in this study. BaMV is a single‐stranded, positive‐sense RNA virus. This gene product, designated as NbTRXh2, was matched with sequences of thioredoxin h proteins, a group of small proteins with a conserved active‐site motif WCXPC conferring disulfide reductase activity. To examine how NbTRXh2 is involved in the infection cycle of BaMV, we used the virus‐induced gene silencing technique to knock down NbTRXh2 expression in N. benthamiana and inoculated the plants with BaMV. We observed that, compared with control plants, BaMV coat protein accumulation increased in knockdown plants at 5 days post‐inoculation (dpi). Furthermore, BaMV coat protein accumulation did not differ significantly between NbTRXh2‐knockdown and control protoplasts at 24 hpi. The BaMV infection foci in NbTRXh2‐knockdown plants were larger than those in control plants. In addition, BaMV coat protein accumulation decreased when NbTRXh2 was transiently expressed in plants. These results suggest that NbTRXh2 plays a role in restricting BaMV accumulation. Moreover, confocal microscopy results showed that NbTRXh2‐OFP (NbTRXh2 fused with orange fluorescent protein) localized at the plasma membrane, similar to AtTRXh9, a homologue in Arabidopsis. The expression of the mutant that did not target the substrates failed to reduce BaMV accumulation. Co‐immunoprecipitation experiments revealed that the viral movement protein TGBp2 could be the target of NbTRXh2. Overall, the functional role of NbTRXh2 in reducing the disulfide bonds of targeting factors, encoded either by the host or virus (TGBp2), is crucial in restricting BaMV movement.